PERANAN BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) DALAM PENYUSUNAN KEBIJAKAN DIBIDANG PEMBANGUNAN - Andri Jasman; Malik Malik (e-JKPP, 2023)
The problems in this research are (1) How the Regional Development Planning Agency (Bappeda) Functions in Developing Policies in the Development Sector of Mesuji Regency is one of the issues with this study. (2) What factors limit the Regional Development Planning Agency's (Bappeda) ability to formulate policies for the Mesuji Regency's development sector. This research design uses qualitative research with qualitative descriptive analysis method. The research design intends to describe and qualitatively examine the Role of the Regional Development Planning Agency (Bappeda) in Formulating Policies in the Development Sector of Mesuji Regency. The findings revealed that: (1) The Regional Development Planning Agency's (Bappeda) role in developing policies for the Mesuji Regency's development sector has been carried out in accordance with its role as a formal authority. Strategic decisions, development planning based on the bottom-up principle, namely the process of compiling development plans from the District and Regional Apparatus Organizations (OPD) by taking into account the needs and aspirations that are prioritized, and top-down planning with the principle that the process of formulating development plans in the District and OPD, it needs to synergize